Influence of Classroom Environment, Lecturer Competence, and ICT Resources on Perceived Academic Performance Mediated by Student Engagement - Leny Noviani; Nahda Amalia Putri; Leny Kurnia Oktaviani (Economics Education Department Universitas Negeri Semarang, 2025)
This study was done to analyze the influence of student engagement on the perception of academic performance; the classroom environment perception on student engagement; the lecturer competence perception on student engagement; the ICT resources perception on student engagement; and the classroom environment perception, lecturer competence, and ICT resources on the perception of academic performance mediated by student engagement. This study employs a quantitative descriptive method, analysing data from questionnaires collected from 395 students selected through probability sampling with proportionate random sampling. Data analysis techniques included descriptive statistics, regression analysis, collinearity diagnostics (VIF), significance tests, and model fit. The results indicate that student engagement has a positive and significant impact on academic performance; classroom environment has a positive and significant impact on student engagement; lecturer competence has a positive and significant impact on student engagement; ICT resources has a positive and significant impact on student engagement; classroom environment has a positive and significant impact on academic performance mediated by student engagement; lecturer competence has a positive and significant impact on academic performance mediated by student engagement; also ICT resources has a positive and significant impact on academic performance mediated by student engagement. These findings suggest that higher education institutions should prioritize engagement-oriented learning strategies by enhancing lecturers’ pedagogical competence, optimizing ICT resources, and improving classroom learning environments to enhance students’ academic performance.